Demographic Factor Influence in the Supply Chain Strategies and Economic System - Imideeva, Irina; Aiyzhy, Elena; Badaraeva, Renata; Liktan, Valeriana; Manchyk - Sat, Choduraa (International Journal of Supply Chain Management, 2020)
Abstract— The great majority of companies' supply chains span multiple countries, cultures, and industries. However people in different parts of the globe perceive supply chain risks differently. The research is intended to identify patterns of the socio-economic situation and the characteristics of the development of the demographic situation in the economic system through supply chain strategies, as well as present the factors of ensuring demographic in the industries development. Various methods of statistical, economic-mathematical, and sociological analysis were used in the study. The main trends in migration processes and patterns of development of the demographic situation in the world, country, and economic situations were identified. The dynamics of the Gross domestic product (GDP) of Russia was analyzed as well. The results of a retrospective analysis of population dynamics, changes in Gross domestic product depending on the population are shown. The relationship between the demographic and supply chain strategies of the state and its economic and political security is revealed. The analysis shows that there are indeed demographic factors that can help predict how people manage supply chain risk. The results obtained during the study can serve as the basis for the development of more advanced socio-economic policies both at the regional and interregional levels of economic development through supply chain strategies, which one of the main factor in supply chain is population.